49.6k views
4 votes
Y = 5x - 3
10x - 2y = 7

User BonJon
by
4.9k points

1 Answer

2 votes

Answer:

No solution

Explanation:

First I plugged the value of y into the equation 10x-2y=, which gave me
10x- 2(5x - 3) = 7. Then you can distribute the -2 into the parenthesis giving you 10x - 2(5x)(-2 x -3) = 7. This leaves us with 10x- 10x + 6 = 7, because two negatives multiplied together form a positive. Now you subtract six from both sides to keep it equal, and you're left with 10x-10x= 1. This gives you 0= 1, which is not possible, so there is no solution.

We can check our work by putting 10x -2y= 7 into y=mx+b format, by subtracting 10x from both sides, leaving you with -2y = -10x+ 7. then you can divide out the -2, giving you y= 5x+ 7/5. Notice how the slopes in both our equations are 5x. This means that they are a group of parallel lines, bc they both stay at the same rate, despite having different y-intercepts or starting points.

I hope this helps and please let me know if you have any other questions or need somethign to be explained more :D

User Shmsi
by
5.4k points